2006
DOI: 10.1164/rccm.200507-1161ws
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Oxygen Treatment in Chronic Obstructive Pulmonary Disease: Recommendations for Future Research

Abstract: Long-term oxygen treatment (LTOT) prolongs life in patients with chronic obstructive pulmonary disease (COPD) and severe resting hypoxemia. Although this benefit is proven by clinical trials, scientific research has not provided definitive guidance regarding who should receive LTOT and how it should be delivered. Deficiencies in knowledge and in current research activity related to LTOT are especially striking in comparison to the importance of LTOT in the management of COPD and the associated costs. The Natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
110
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(116 citation statements)
references
References 42 publications
0
110
0
6
Order By: Relevance
“…Healthcare systems in many countries include public funding of LTOT for eligible applicants [55]. The role of LTOT and of acute oxygen supplementation during an AECOPD are described elsewhere in the current series [56].…”
Section: Transcutaneous Neuromuscular Electrical Stimulationmentioning
confidence: 99%
“…Healthcare systems in many countries include public funding of LTOT for eligible applicants [55]. The role of LTOT and of acute oxygen supplementation during an AECOPD are described elsewhere in the current series [56].…”
Section: Transcutaneous Neuromuscular Electrical Stimulationmentioning
confidence: 99%
“…In these patients the primary goal of oxygen therapy is the avoidance of hypoxemia, and the use of oxygen is quite liberal, because the risks of side effects associated with hyperoxemia or exposure to high F IO 2 are generally considered to be small. There are, however, emerging concerns, including the association between both hyperoxemia and hypoxemia, with increased risk of death post cardiac arrest 20 and increased death or worse outcome in severe head trauma. 21 Clinicians suggest potential benefits of F IO 2 titration in lieu of a continuously high F IO 2 , independent of the arterial oxygen levels, 22,23 and potential risks due to masking of the onset of worsening in lung function by hyperoxemia.…”
Section: Introductionmentioning
confidence: 99%
“…The NHLBI working group reported that approximately 1 million patients receive LTOT through the Medicare program with reimbursements for oxygen exceeding $2 billion/y. 25 The working group also reported that reimbursements for oxygen were increasing by 12-13%/y. 25 In our model, we can assume that nearly half of the oxygen delivered from the flow meter was not delivered to the lower airway.…”
Section: Discussionmentioning
confidence: 99%
“…25 The working group also reported that reimbursements for oxygen were increasing by 12-13%/y. 25 In our model, we can assume that nearly half of the oxygen delivered from the flow meter was not delivered to the lower airway. Given this same scenario for the LTOT patient, it seems reasonable to conclude that an undetermined amount of oxygen and health-care dollars are actually providing incomplete benefits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation